Modifications of medical treatment and outcome after percutaneous correction of secondary mitral regurgitation. (19th May 2020) - Stolfo, Davide; Castrichini, Matteo; Biagini, Elena; Compagnone, Miriam; De Luca, Antonio; Caiffa, Thomas; Berardini, Alessandra; Vitrella, Giancarlo; Korcova, Renata; Perkan, Andrea; Foroni, Marco; Merlo, Marco; et al.
Abstract: Aims: The optimization of guideline‐directed medical therapy (GDMT) in reduced ejection fraction heart failure (HFrEF) is associated with improved survival and can reduce the severity of secondary mitral regurgitation (SMR). Highest tolerated doses should be achieved before percutaneous mitral valve repair (pMVR) and drugs titration further pursued after procedure. The degree of GDMT titration in patients with HFrEF and SMR treated with pMVR remains unexplored. We sought to evaluate the adherence to GDMT in HFrEF in patients undergoing pMVR and to explore the association between changes in GDMT post‐pMVR and prognosis. Methods and results: We included all the patients with HFrEF and SMR ≥ 3 + treated with pMVR between 2012 and 2019 and with available follow‐up. GDMT, comprehensive of dosages, was systematically recorded. The study endpoint was a composite of death and heart transplantation. Among 133 patients successfully treated, 121 were included (67 ± 12 years old, 77% male patients). Treatment rates of angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers/angiotensin receptor neprilysin inhibitor (ACEIs/ARBs/ARNI), beta‐blockers, and mineralcorticoid receptor antagonist at baseline and follow‐up were 73% and 79%, 85% and 84%, 70% and 70%, respectively. At baseline, 33% and 32% of patients were using >50% of the target dose of ACEI/ARB/ARNI and beta‐blockers. At follow‐up (median time 4 months), 33% of patients unchanged, 34% uptitrated, and 33% of patients downtitrated GDMT. Downtitration of GDMT was independently associated with higher risk of death/heart transplantation (hazard ratio: 2.542, 95%confidence interval: 1.377–4.694, P = 0.003). Conclusions: Guideline‐directed medical therapy is frequently underdosed in HFrEF patients with SMR undergoing pMVR. Downtitration of medications after procedure is associated with poor prognosis.